Ixodidae (Acari: Ixodoidea): descriptions and redescriptions of all known species from 1758 to December 31, 2019 - Guglielmone, Alberto; Petney, Trevor; Robbins, Richard G. (Magnolia Press, 2020)
References to the descriptions and redescriptions of the 742 species of Ixodidae published from 1758 to December 31, 2019 are compiled, with the goal of enabling tick taxonomists to readily access this diffuse and often confusing literature. Additionally, data resulting from this effort are critically analyzed to demonstrate the problems attending correct identification of several tick species that are of medical, veterinary and/or evolutionary importance, and to highlight the need for new or enhanced diagnostic techniques. Recent morphological and molecular studies indicate that some ixodid species names represent more than one taxon; therefore, it is expected that new species will be described in the near future, based partly on material already deposited in museums around the world.